Understanding the mechanism by which nitrilotriacetic acid interacts with precipitating barium sulfate - Jones, Franca; Oliveira, Allan; Rohl, Andrew; Ogden, Mark; Parkinson, Gordon (Royal Society of Chemistry, 2006)
Morphology modifiers can act in many different ways on the precipitating phase. Inhibitors can alter the solution chemistry and thereby change the supersaturation, they may adsorb onto the surface and block growth and agglomeration, they may alter the ritical nucleus and affect nucleation or they may do a combination of these three. revious work showing that nitrilotriacetic acid (NTA) had a significant effect on barium sulfate precipitation has been expanded upon in order to determine the mechanism by which the observed morphology modification occurs. The absence of significant complexation to barium at the pH of the experiment suggests that NTA affects the critical nuclei of the precipitating barium sulfate. This results in the longer induction times observed using nephelometry, and adsorption onto growth features is probably the mechanism of interaction. Molecular modelling shows that NTA adsorption is favourable on terraces and that hydrogen bonding improves the ability of an additive to adsorb. A fundamental nderstanding of the mechanisms by which additives affect crystal growth is essential if new additives, with predictable effect, are to be designed a priori.